Non linear failure of corbel for IBS blockwork - Abd. Latif, Muhamad Faiz (2014)
IBS technology grows rapidly around the world. One of the frequent topic discuss now is the flexibility of blockworks are to be assemble to form a house quickly. This study present the behaviour of T-shape and L-shape full scale blockwork. The Autodesk Multiphysics finite element software was used to develop the blockwork element modelling. The mechanism of failure was obtained by comparing the results between experimental and finite element analysis output. The laboratory test was to find the failure criteria at certain load levels within three load cycle approach. From the displacement obtained, the coefficient of friction can be determined. The result shown that the mechanism of failure obtain from modelling is similar as laboratory test. But, the percentage different between laboratory test and finite element analysis software was far too great and the coefficient of friction could not be calculated.